2021
DOI: 10.3390/v13122504
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Out of Retrovirus Receptor Gene Tva in the Chicken Confers Resistance to Avian Leukosis Virus Subgroups A and K and Affects Cobalamin (Vitamin B12)-Dependent Level of Methylmalonic Acid

Abstract: The chicken Tva cell surface protein, a member of the low-density lipoprotein receptor family, has been identified as an entry receptor for avian leukosis virus of classic subgroup A and newly emerging subgroup K. Because both viruses represent an important concern for the poultry industry, we introduced a frame-shifting deletion into the chicken tva locus with the aim of knocking-out Tva expression and creating a virus-resistant chicken line. The tva knock-out was prepared by CRISPR/Cas9 gene editing in chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…Tva is involved in TC-mediated Cbl uptake ( 29 ). Although Tva-deficient gene-edited chickens have been generated and could completely resist ALV-K infection, they exhibit specific Cbl metabolic disturbances due to the lack of Tva ( 42 ). In this study, E53, L55, H59, and G70 were identified as the key residues for Tva to interact with gp85 and mediate ALV-K entry into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tva is involved in TC-mediated Cbl uptake ( 29 ). Although Tva-deficient gene-edited chickens have been generated and could completely resist ALV-K infection, they exhibit specific Cbl metabolic disturbances due to the lack of Tva ( 42 ). In this study, E53, L55, H59, and G70 were identified as the key residues for Tva to interact with gp85 and mediate ALV-K entry into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported data demonstrate that the avian TVA receptor protein belongs to the LDLR family, is an ortholog of mammalian CD320, and acts as a vitamin B 12 transporter as well as a viral receptor (Krchlikova et al, 2021). Further, tva knockout chickens generated using CRISPR/Cas9 technology are not only resistant to ALV-A and -K, but also exhibit vitamin deficiency (Koslova et al, 2021). Growth retardation due to vitamin deficiency was not observed in KO and KNC individuals resistant to ALV subgroups, and further studies are needed to determine whether there are other genes that can compensate for lack of vitamin uptake by the TVA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deletion of nucleotides in the intronic region of the chicken tva gene (tva r3 , tva r4 , tva r5 , and tva r6 ) affects the branch point signal involved in splicing, resulting in incomplete mRNA splicing and decreased susceptibility to ALV-A (Reinisova et al, 2012;Chen et al, 2015). Further, recent findings demonstrate that ALV-K shares the TVA receptor with ALV-A (Prikryl et al, 2019), and knockout of Tva in chicken using the CRISPR/Cas9 system confers resistance to both ALV-A and -K (Koslova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These deletions disrupt mRNA splicing of the Tva receptor gene and prematurely introduced the TGA stop codon, thereby reducing sensitivity to ALV-A [ 77 , 78 ]. Recent findings have demonstrated that ALV-A and ALV-K-resistant individuals can be produced after Tva knockout in chicken primordial germ cells (PGCs) using CRISPR/Cas9 gene editing technology [ 79 ].…”
Section: Alv Cannot Invade Host Cells Until It Binds To Viral Receptorsmentioning
confidence: 99%
“…In other words, the mutation NHE1 ΔW38 mediates the chicken resistance against HPRS-103, and the W38 deletion has no negative effects on chicken growth and health [ 175 177 ]. Furthermore, using the same method, a transgenic commercial chicken line resistant to ALV-A/K was obtained [ 79 ]. Those results shows that the viral receptor of ALV is not necessary in the growth cycle of chickens, and it can be eliminated to obtain resistance (Fig.…”
Section: Strategies and Techniques Of Disease-resistant Breeding For Alvmentioning
confidence: 99%